Quarter-life crisis: Personal growth initiative as a moderator of uncertainty intolerance in psychological distress - Balqis, Audita Izza; Karmiyati, Diah; Suryaningrum, Cahyaning; Akhtar, Hanif (Faculty of Psychology and Health - Universitas Islam Negeri Walisongo Semarang, 2023)
Quarter-life crisis is a psychosocial crisis in which individuals are vulnerable to experiencing psychological distress. One contributor to such distress is uncertainty intolerance, while personal growth initiative is a factor that can reduce it. This study examines Personal Growth Initiative (PGI) in determining the effect of uncertainty intolerance on psychological distress in individuals experiencing a quarter-life crisis. A total of 309 participants were selected through a screening process using the Quarter-life Crisis Questionnaire. The participants completed the Intolerance of Uncertainty Scale, General Health Questionnaire-12, and Personal Growth Initiative Scale. Moderation regression analysis was performed using the Hayes PROCESS Macro. The results indicate that personal growth initiative buffers the effect of uncertainty intolerance on psychological distress in individuals experiencing a quarter-life crisis (B = -0.193, p = .003, R2 = .117), but with differences shown based on age and gender categories. Based on the findings, it is necessary to build personal growth initiative skills, which will assist individuals in achieving and maximizing their potential and adapting well when faced with conditions of uncertainty.